Women as Agents of Change : Having Voice in Society and Influencing Policy - Markham, Susan (World Bank, Washington, DC, 2014)
The World Bank's World Development Report (WDR) on gender equality and development identified women's voice, agency, and participation as a key dimension of gender equality and as a major policy priority. Agency, as defined in the WDR2012, is the ability to use endowments to take advantage of opportunities to achieve desired outcomes. In particular, WDR2012 focused on five expressions of agency: women's access to and control over resources; freedom of movement; freedom from the risk of violence; decision-making over family formation; and having voice in society and influencing policy. An important expression of women's agency is women's political participation and their ability to fully engage in public life. This background paper focuses on women s ability to play a public role in politics and to influence policy-making. Using the data available, it examines the current status of women in politics and makes the case for the full and equitable participation of women in public life. It reviews the direct and indirect barriers that exist to prevent women's political participation and analyzes strategies that have been used to increase it. Finally, the paper identifies the connections between the five expressions of agency and priorities for future work.